QISHÂSH: HUKUMAN MATI DALAM PERSPEKTIF AL-QURAN - Chuzaimah Batubara (State Islamic University North Sumatra, 2010)
Abstract: Qishâsh: Capital Sentence in Qur’anic Perspective. A great deal of controversy exists globally over capital sentencing or death penalty, which has a number of staunch opponents and defenders. In Islam, however, although a number of the text of revelations deals with such an issue, typically, capital crimes are very carefully outlined in the works of Qur’anic exegetes and Islamic legal scholars. The author argues that Islam guarantees and protects every single life and thus capital sentence should be used in very rare cases and should be avoided as much as possible, but this does not necessarily mean to stop the possibility of it entirely. In addition, if capital sentence is finally justified and executed this is not aimed at killing people but rather maintaining and protecting lives from threatening forces. This paper is an attempt to analyze the Qur’anic verses thematically pertaining to capital sentence, how they should be understoodand practiced.Kata Kunci: hukuman mati, qishâsh, al-Qur’an